La importancia de los lazos sociales: clases sociales y mecanismos de acceso al empleo en el Área Metropolitana de Buenos Aires - Carrascosa, Joaquín (El Colegio de México, 2020)
This paper analyzes differences between social classes in the use of job access mechanisms in the Metropolitan Area of Buenos Aires. A distinction is made between mechanisms based on the mobilization of social ties linked to various spheres of socialization such as family, neighborhood, school, university and workplace and job finding without the use of these ties. The paper also analyzes the relationship between the use of social ties and access to formal or informal jobs and the differences in the use of ties according to the trajectories of intergenerational and intragenerational social mobility toward the middle class. Quantitative methodology is used with data from the PI-Clases survey Reproduction and social mobility in family trajectories and life courses (2015-2016). Both strong and weak ties proved crucial to obtaining access to employment.  The latter include the importance of former colleagues and neighborhood ties for working-class people.  However, in the working class and for non-manual laborers, the use of social ties is linked to informal jobs. Moreover, those who are intergenerationally stable in the middle class largely use their family ties, which suggests class reproduction mechanisms through social capital.